Toponymy of Gampong Names in Bandar Dua District, Pidie Jaya Regency - Irmayana Irmayana; Mohd. Harun; Maya Safhida (Universitas Muria Kudus, 2026)
This study aims to describe the toponymy of village (gampong) names in Bandar Dua District, Pidie Jaya Regency based on their naming aspects. This research employs a descriptive qualitative method. The data of this study consist of informants’ narratives containing the origins of village naming in Bandar Dua District, Pidie Jaya Regency. The data sources are informants who are native residents and local traditional leaders. Data were collected through observation and interviews. The results show that the toponymy of village names in Bandar Dua District, Pidie Jaya Regency is based on three naming aspects: the embodiment aspect, the social aspect, and the cultural aspect. There are 37 villages referring to the embodiment aspect, 21 villages referring to the social aspect, and one village referring to the cultural aspect in their naming.